Gedenktafeln für die Galeerensklaven des Reformierten Kollegiums Sárospatak - Pálfi, Edina (Acta Neerlandica, 2026)
Sárospatak is a prominent academic town in eastern Hungary, where three memorialplaques were unveiled between 1936 and 1939 in memory of the galley slaves. The collegeitself is a place of remembrance, representing 500 years of Protestant culture. There arememorial plaques here to the school’s patrons, former teachers, scholars, and the manytraumas of the 20th century (World War I and II, Trianon, the Gulag camps). It is thereforesurprising that, among the eight other memorial plaques located at the entrance, threeplaques commemorate the galley slaves. The study explores the context of their creation,the idea, the application, and the unveiling, and interprets the phenomenon. The history ofgalley slavery contains not only religious but also national elements of memory, and wassuitable for depicting the world of great cataclysms and tragedies in every age, as well asfor analogically showing the ways of escaping from them.